2018
DOI: 10.1016/j.repc.2017.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Análise comparativa do fractional flow reserve (FFR) e do instantaneous wave‐free ratio (iFR): resultados de um registo de 5 anos

Abstract: iFR had a reasonable diagnostic performance. Operators often chose to perform FFR despite conclusive iFR results. iFR and FFR were highly concordant, but a non-negligible proportion of lesions classified as ischemic by iFR were classified as non-ischemic by FFR. iFR had no impact on procedural characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This value is slightly higher than reported in previous studies [ 34 ]. However, other studies reported a higher [ 15 ] and a similar optimal cut-off value when comparing FFR with iFR [ 35 ]. Similarly, the optimal cut-off value for FFR to detect significant ischemia based on iFR/RFR (iFR/RFR ≤ 0.89) was 0.82.…”
Section: Discussionmentioning
confidence: 87%
“…This value is slightly higher than reported in previous studies [ 34 ]. However, other studies reported a higher [ 15 ] and a similar optimal cut-off value when comparing FFR with iFR [ 35 ]. Similarly, the optimal cut-off value for FFR to detect significant ischemia based on iFR/RFR (iFR/RFR ≤ 0.89) was 0.82.…”
Section: Discussionmentioning
confidence: 87%
“…12 , 13 However, some studies have shown that there can be some inconsistencies between the two measurements. 14 In a provocative article published in Rev Port Cardiol, Menezes et al 15 report their experience directly comparing FFR and iFR information in 150 patients. They have demonstrated that, in general, FFR and iFR are concordant, but in a significant proportion of cases (13%) the results differed between the two techniques.…”
Section: Coronary Artery Diseasementioning
confidence: 99%